Comparison of Surface-Enhanced Raman Scattering in Colloidal Silver Nanostar ‎and Colloidal Silver Nanocubes - Zinah Salahuddin Shakir; Sameer Khudhur Yaseen; Ayad Abdul Razzak Dhaigham (مجلة بغداد للعلوم)
Surface-enhanced Raman spectroscopy (SERS) is an extremely responsive and selective method that improves the Raman scattering signals of molecules utilizing nanomaterials as substrates. SERS enables the identification of material in very low concentrations via electrical field amplification or chemical enhancement due to the localized surface Plasmon (LSP).  In this work, low concentrations of sodium sulfate (Na2SO4) were investigated as a water pollutant using liquid SERS based on colloidal Ag nanostructures.  Two types of Ag nanostructures were prepared and utilized as liquid SERS substrates: nanostars (NSs) and nanocubes (NCs).  A chemical reduction method was used for synthesizing Ag nanostructures from silver ions using reducing agents.  An atomic force microscope (AFM) and Scanning Electron Microscope (SEM) were employed to characterize the nanosilver.  The SERS actions of these nanostructures in detecting sodium sulfates were reported and analyzed concerning both shape and size using a 532 nm diode-pumped solid-state laser.  We observed that nanostructures with more and more shaped corners gave stronger SERS signals.  The increase in the SERS signal is related to LSP, which results from the deposition of sodium sulfate molecules in the hotspots (spaces between aggregated silver nanostructures) in the solution. Raman peaks intensify as the sulfate concentration increases.  The proposed AgNS colloid provides stronger SERS activity than the AgNC colloid.  This means that AgNS as liquid SERS substrates are more efficient at detecting low concentrations of analytes than AgNC.  The highest sulfate analytical enhancement factor (AEF) obtained for SERS in both colloids, AgNS and AgNC, were at the lowest concentrations (7x10-7 M), which were 2.6 x103 and 1.7x 103, respectively.